Comparison of PTCH1, COX‐2, p53, and Ki‐67 protein expression in basal cell carcinomas of nodular and superficial subtypes arising on the head and trunk. (28th April 2016) - Khalesi, Mohammad; Waterhouse, Mary; Whiteman, David C.; Johns, Richard; Rosendahl, Cliff; Hackett, Timothy; Pollak, Thomas; Kimlin, Michael G.; Hacker, Elke; Neale, Rachel E.; ,
Abstract: Background: There is some evidence that basal cell carcinomas (BCCs) arising on different anatomic sites and developing to different histological subtypes differ in their pathophysiology. The expression of a number of proteins, including PTCH1, COX‐2, p53, and Ki‐67, is frequently altered in BCC development. Objectives: This study sought to determine whether protein expression differs between BCCs at different anatomic sites and of different histological subtypes. Methods: Expression of PTCH1, COX‐2, p53, and Ki‐67 proteins was compared between: (i) BCCs arising on the head ( n = 55) and trunk ( n = 53), and (ii) nodular ( n = 52) and superficial ( n = 43) BCCs. The intensity of immunohistochemistry (IHC) staining (low, moderate, strong, very strong) for PTCH1 and COX‐2 proteins was measured and the proportions of p53‐ and Ki‐67‐positive cells quantified. Results: The proportion of cells expressing Ki‐67 was higher in tumor tissue than in non‐malignant epidermis, whereas the opposite was found for PTCH1. The IHC staining intensity for PTCH1 was substantially greater in truncal BCCs than in BCCs on the head (odds ratio [OR] 3.82, 95% confidence interval [CI] 1.63–8.96). The intensity of staining for PTCH1 was greater for superficial than for nodular BCCs (OR 3.70, 95% CI 1.53–8.97), and superficial BCCs showed a higher proportion of Ki‐67‐positive cells (OR 5.57, 95% CI 1.66–18.67). Conclusions: These differences suggest that the pathophysiology of BCC differs between lesions on the head and trunk and between nodular and superficial subtypes, perhaps indicating differences in their etiology.